INTEGRASI MODEL PEMBELAJARAN BERBASIS BUDAYA DAN KEARIFAN LOKAL DALAM KURIKULUM MADRASAH IBTIDAIYAH: ANALISIS LITERATUR TERHADAP PENDEKATAN, STRATEGI, DAN IMPLEMENTASINYA DI LINGKUNGAN PENDIDIKAN DASAR ISLAM - Afifah, Fatma Zahro’ul; Purbasari, Ariya Ayu; Paradina, Ines; Rachmania, Rachmania; Afifah, Amilatul; Suttrisno, Suttrisno (STKIP Pesisir Selatan, 2025)
The integration of culture and local wisdom in Madrasah Ibtidaiyah (MI) learning is a strategic effort to strengthen the identity of learners and increase the relevance of the curriculum to the surrounding social and cultural environment amid globalization. This research aims to analyze the models, strategies, and implementation of culture and local wisdom-based learning applied in MI as an effort to enrich the Islamic basic education curriculum with a qualitative approach through literature studies from relevant journals, articles, and educational documents for the 2015-2025 period. The analysis results show that models such as Contextual Teaching and Learning (CTL), Project-Based Learning (PjBL), and ethnopedagogy have been successfully adapted contextually in MI by involving the collaboration of teachers, students, and local communities. Learning strategies emphasize the integration of local content and out-of-class project activities that strengthen learners' cultural engagement and character. The main challenges include limited teacher competence in contextual learning, lack of local cultural learning resources, and not optimal supporting curriculum policies. Therefore, systemic support is needed in the form of teacher training, preparation of locality-based teaching tools, and curriculum policies that encourage flexibility and autonomy of madrasah.